2009
DOI: 10.1016/j.envres.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Infant exposure to fine particulate matter and traffic and risk of hospitalization for RSV bronchiolitis in a region with lower ambient air pollution

Abstract: Few studies investigate the impact of air pollution on the leading cause of infant morbidity, acute bronchiolitis. We investigated the influence of PM2.5 and other metrics of traffic-derived air pollution exposure using a matched case–control dataset derived from 1997 to 2003 birth and infant hospitalization records from the Puget Sound Region, Washington State. Mean daily PM2.5 exposure for 7, 30, 60 and lifetime days before case bronchiolitis hospitalization date were derived from community monitors. A regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 16 publications
3
75
0
Order By: Relevance
“…Several studies have found an association between PM 2.5 and infant bronchiolitis, an important risk for hospitalization (Karr et al, 2007(Karr et al, , 2009a. Exposure to PM 2.5 has also been linked to low lung function in 4-year-old children in a birth cohort study in the Netherlands (Eenhuizen et al, 2012), supporting previously published studies that reported effects of PM 2.5 on lung function development, reviewed in Götschi et al (2008).…”
Section: Critical Data Gapssupporting
confidence: 73%
“…Several studies have found an association between PM 2.5 and infant bronchiolitis, an important risk for hospitalization (Karr et al, 2007(Karr et al, , 2009a. Exposure to PM 2.5 has also been linked to low lung function in 4-year-old children in a birth cohort study in the Netherlands (Eenhuizen et al, 2012), supporting previously published studies that reported effects of PM 2.5 on lung function development, reviewed in Götschi et al (2008).…”
Section: Critical Data Gapssupporting
confidence: 73%
“…However, these models are more suitable for long-term, chronic exposure studies, due to their aggregative nature, and the possible loss of short-term localized measurements needed for more acute exposure incidents (Karr et al, 2009;Brauer, 2010). A better solution may be to use a denser array of sensing nodes, and thus create a better interpolation, closer to the real-life pollution dispersion scenario (Kanaroglou et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…The risk of bronchiolitis is also higher for infants living with older siblings, attending a day-care centre or exposed to environmental tobacco smoke [2,7]. Since ambient air pollution appears to play, if any, a marginal role [8], factors driving the rise of the disease in industrialised countries remain largely unknown.…”
mentioning
confidence: 99%